2019
DOI: 10.1183/13993003.00585-2019
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical phenotypes and outcomes of precapillary pulmonary hypertension of sickle cell disease

Abstract: RationalePrecapillary pulmonary hypertension (PH) is a devastating complication of sickle cell disease (SCD). Little is known about the influence of the SCD genotype on PH characteristics.ObjectivesTo describe clinical phenotypes and outcomes of precapillary PH due to SCD according to disease genotype.MethodsA nationwide multicentre retrospective study including all patients with SCD-related precapillary PH from the French PH Registry was conducted. Clinical characteristics and outcomes according to SCD genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…The link between chronic thromboembolic disease and PH in SCD remains unclear. A recently published case series of 58 patients with sickle cell disease and precapillary PH found mismatched segmental perfusion defects on lung scintigraphy in 85% of HbSC patients and 9% of HbSS/S‐β0 thal patients, respectively 23 . To further explore this observation, we performed a subgroup analysis of subjects diagnosed with CTEPH and following PDE5‐I therapy, found no significant difference in mortality ( P = .28), or NYHA class ( P = .36) compared with subjects without evidence of CTEPH.…”
Section: Discussionmentioning
confidence: 99%
“…The link between chronic thromboembolic disease and PH in SCD remains unclear. A recently published case series of 58 patients with sickle cell disease and precapillary PH found mismatched segmental perfusion defects on lung scintigraphy in 85% of HbSC patients and 9% of HbSS/S‐β0 thal patients, respectively 23 . To further explore this observation, we performed a subgroup analysis of subjects diagnosed with CTEPH and following PDE5‐I therapy, found no significant difference in mortality ( P = .28), or NYHA class ( P = .36) compared with subjects without evidence of CTEPH.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 24 25 ] Both pre and postcapillary PH are seen in PH-SCD, however, the precapillary component has been reported to be slightly more prevalent in previous studies[ 26 27 ] and is associated with poor prognosis. [ 26 28 ] Chronic thromboembolism and intravascular hemolysis leading to nitric oxide depletion and endothelial dysfunction are major contributors to precapillary PH-SCD. A recent study has shown a high prevalence of mismatched segmental perfusion defects in VQ scintigraphy and advocates the use of VQ scan for CTEPH screening in this population.…”
Section: Discussionmentioning
confidence: 99%
“…There are five different groups of PH: 1) pulmonary arterial hypertension, 2) PH due to left heart disease, 3) PH due to chronic lung disease/hypoxia, 4) PH due to chronic pulmonary thromboembolisms, and 5) PH due to unclear multifactorial mechanisms. PH related to SCD is currently in group 5 as some patients show hemodynamic changes consistent with group 1, while others have features of group 2 or group 4 PH [50,51].…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%